FAKTOR-FAKTOR DETERMINAN PARTISIPASI MASYARAKAT (D/S) DI WILAYAH PUSKESMAS GABUS I, KABUPATEN GROBOGAN - Sishayati Sishayati; Sunarto Sunarto (JURNAL RISET GIZI, 2016)
Background : Health Integrated Comprehensif (Posyandu) is important in monitoring for infants, toddlers and the role of his mother. Efforts to increase coverage of D/S (level partisipasion) to Posyandu are expected under five suffering from malnutrition and malnutrition can be detected so quickly to do intervention measures and countermeasures. Puskesmas Gabus I Grobogan in two consecutive years 2014 and 2015 have not reached the standard SPM and achievements 76.8% and 77.8%. Methods : The study by cross sectional on the 46 mothers, toddler age 12-24 months. Statistical analysis using Chi-square test and logistic regression test. Results : The results showed 50% of women participate actively and 50% inactive to Posyandu, means participation in the region Puskesmas I considered optimal. Most educated respondents Basic 30 respondents, 31 respondents out of work, 27 respondents knowledgeable unfavorable. 13 respondents working and inactive to the Posyandu. 19 respondents had knowledgeable less well and had no active participation. 17 respondents whose families are less active support and participation, and there are 15 respondents who had PMT unfavorable perception and also inactive. There is a relationship between education, employment, knowledge, family support and the perception PMT of the level of community participation (D / S) to the Posyandu. The most dominant factor affecting the level of community participation in sequence as follows: education, employment, knowledge, family support, and perceptions PMT with value (p value 0.000; 0.001; 0.052; 0.089; 0.992). Conclusions : education, employment, knowledge, family support, and perceptions PMT have a relationship and influence on the level of participation (D/S), so it is still necessary to increase outreach activities and health promotion efforts more to increase mother visits to Posyandu